Cylindrical lithium battery and preparation method thereof

By designing cylindrical lithium batteries, using coated high-nickel transition metal oxide materials and graphite materials, and forming a metal lithium layer during the charging process, the problem of insufficient storage performance and power density of traditional lithium batteries is solved, and long-term maintenance-free storage and high-power discharge characteristics are achieved.

CN119601752APending Publication Date: 2025-03-11SHANGHAI INST OF SPACE POWER SOURCES +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411831252.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional lithium batteries have shortcomings in storage performance and power density, and require regular maintenance, which cannot meet the long-term maintenance-free application needs.

Method used

By designing a cylindrical lithium battery, a coated high-nickel transition metal oxide material is used as the positive electrode active material and a graphite material is used as the negative electrode active material, and a metal lithium layer is formed during the battery charging process, and fluoroic acid anhydride compounds are added to the electrolyte to inhibit side reactions.

Benefits of technology

It has achieved maintenance-free storage for more than 10 years of full-charge electricity, and has high specific energy and high power discharge characteristics to meet application needs, while reducing self-discharge rates and increasing battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601752A_ABST
    Figure CN119601752A_ABST
Patent Text Reader

Abstract

The invention discloses a cylindrical lithium battery and a preparation method thereof, the cylindrical lithium battery comprises a battery shell, a battery cap, a battery cell and an electrolyte, the battery cell is composed of a positive electrode, a negative electrode and a diaphragm, and an active material of the positive electrode is a coated high-nickel transition metal oxide material; the active material of the negative electrode is graphite, the negative electrode contains a first coating and a second coating, and a third coating-metal lithium layer is formed inside and on the surface of the second coating of the negative electrode when the battery is charged to be between the first voltage U1 and the second voltage U2; the first coating is made of a graphite material, and the second coating is made of a porous conductive material; the first voltage U1 ranges from 3.85 V to 4.00 V, and the second voltage U2 ranges from 4.1 V to 4.3 V. The lithium battery provided by the invention has the dual advantages of low self-discharge rate of a lithium primary battery and high-power discharge of a lithium ion battery, and the preparation method is simple to operate, does not increase additional treatment procedures, and almost has no influence on the battery cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical batteries and relates to a cylindrical lithium battery and a preparation method thereof, and specifically relates to a reserve lithium battery and a preparation method thereof. Background Art

[0002] Traditional lithium primary batteries use metallic lithium as the negative electrode, and the battery power performance is poor, generally only having a 1-3C discharge capacity. Although conventional lithium-ion batteries have high energy density and high power density, the battery storage performance is not high, and its monthly self-discharge rate is as high as 3-5%. The maintenance-free storage life is only 1-3 years. Regular maintenance is often required during use, which cannot meet the long-term maintenance-free application requirements. The battery storage life can be extended by setting an activation device, but the activation time is long, it is difficult to judge the battery status before activation, and the maximum power output cannot be achieved immediately after activation, which affects the use. Summary of the invention

[0003] The purpose of the present invention is to provide a cylindrical lithium battery and a preparation method thereof, which can achieve more than 10 years of full-charge maintenance-free storage by adjusting the battery design and optimizing the formation process, and at the same time have high specific energy and high-power discharge characteristics to meet application requirements.

[0004] The objective of the present invention is achieved through the following technical solutions:

[0005] A cylindrical lithium battery, comprising a battery shell, a battery cap, a battery cell, and an electrolyte, wherein the battery cell is composed of a positive electrode, a negative electrode, and a diaphragm, wherein:

[0006] The active material of the positive electrode is a coated high-nickel transition metal oxide material;

[0007] The coated high-nickel transition metal oxide material is lithium nickel cobalt chromate (NCC, Li 1+x Ni y Co z Cr 1-x-y-z O2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), lithium nickel cobalt manganese oxide (NCM, Li 1+x Ni y Co z Mn 1-x-y-z O2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), lithium nickel cobalt aluminum oxide (NCA, Li 1+x Ni y Co z Al 1-x-y-zO2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), the thickness of the TiNb2O7 coating layer is 0.1-10nm;

[0008] The positive electrode contains at least one of lithium-rich nickel oxide (Li2NiO2), lithium-rich cobalt oxide (Li6CoO4), lithium ferrite (Li5FeO4), lithium squarate (Li2C4O4), and lithium oxalate (Li2C2O4), and the content thereof is 0 to 20 wt%.

[0009] The active material of the negative electrode is graphite, and the negative electrode contains a first coating and a second coating. When the battery is charged to between the first voltage U1 and the second voltage U2, a third coating, a metal lithium layer, is formed inside the second coating of the negative electrode and on the surface of the negative electrode;

[0010] The first coating is a graphite material with a D50 of 8 to 17 μm;

[0011] The surface of the first coating is covered with a second coating, the second coating is a porous conductive material with a porosity of 40% to 99%;

[0012] The porous conductive material includes but is not limited to activated carbon, carbon black, carbon fiber, carbon cloth, conductive polymer, metal porous material, metal organic framework;

[0013] The first voltage U1 is 3.85V to 4.00V, and the second voltage U2 is 4.1V to 4.3V;

[0014] The method for determining the first voltage U1 is as follows: the battery is charged to U2 at 0.1C after liquid injection, and the charging curve is plotted as dQ / dV to V. When the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85V to 4.00V, the voltage at this time is the first voltage U1;

[0015] The method for forming the third coating layer, a metal lithium layer, inside the second coating layer in the negative electrode and on the surface of the negative electrode is as follows: during the charging formation process, lithium is electrochemically deposited on the surface of the negative electrode, and the thickness of the formed metal lithium layer is 1 to 5 μm;

[0016] The reversible capacity ratio per unit area of ​​the negative electrode to the positive electrode of the battery (N / P ratio) is 0.9 to 1.1;

[0017] The electrolyte contains fluorinated anhydride compounds, the addition amount of which is 0.1-5%;

[0018] The fluorinated anhydride compounds include but are not limited to fluorinated acetic anhydride, fluorinated succinic anhydride, fluorinated glutaric anhydride, fluorinated maleic anhydride, and fluorinated benzoic anhydride.

[0019] A method for preparing the above lithium battery comprises the following steps:

[0020] Step S1, mixing the positive electrode active material with the conductive agent and the adhesive evenly and coating the mixture on an aluminum foil, and rolling and cutting the mixture into a positive electrode;

[0021] Step S2, the negative electrode active material is mixed with the conductive agent and the adhesive and then coated on the copper foil, and then a porous conductive layer is coated on the surface after drying, and then the negative electrode is made by roller pressing and slitting, and the N / P ratio of the battery is 0.9-1.1. The battery is formed, and a lithium deposition layer is formed on the surface of the negative electrode in the range of 3.85-4.00V;

[0022] Step S3, winding the positive and negative electrodes and the separator into a cylindrical battery cell, and sequentially performing shelling, cap welding, liquid injection, sealing, and cleaning;

[0023] Step S4, take the battery after injection and charge it at 0.1C to U2, where U2 ranges from 4.1 to 4.3V, preferably 4.2V, plot the charging curve dQ / dV to V, and perform data processing to obtain a smooth curve, and observe the voltage at which the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85 to 4.00V, which is the first voltage U1;

[0024] Step S5, after the battery is filled with liquid, it is allowed to stand for 24 to 72 hours, then charged at a constant current of 0.05C for 1 hour, then charged at a constant current of 0.1C to a first voltage U1, allowed to stand for 10 to 30 minutes, discharged at a constant current of 0.1C to 2.75V, allowed to stand for 10 to 30 minutes, charged at a constant current of 0.2C to a first voltage U1, then charged at a constant current of nC to a second voltage U2, where nC is 0.3 to 2C, switched to constant voltage charging until the current is ≤0.02C, and ended.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. The lithium battery prepared by the present invention is a cylindrical lithium-ion battery, comprising a battery shell, a battery cap, a battery core composed of a positive electrode, a negative electrode, and a separator, and an electrolyte, wherein: the main active material of the positive electrode is a coated high-nickel ternary transition metal oxide material, and the TiNb2O7 coating layer is beneficial to inhibiting the dissolution of the transition metal in the positive electrode material and the side reaction of its electrolyte solution; the main active material of the negative electrode is graphite, and the graphite negative electrode has a composite structure of a first coating and a second coating. During the formation process, between the first voltage U1 and the second voltage U2 of the battery, a third coating metal lithium layer is formed inside and on the surface of the second coating; the electrolyte contains fluorinated anhydride compounds, which effectively inhibit the side reaction of the electrode and the electrolyte by chemically decomposing into a film on the surface of the electrode, thereby improving the storage performance and rate discharge capacity of the battery.

[0027] 2. The lithium battery prepared by the present invention has the dual advantages of low self-discharge rate of lithium primary battery and high power discharge of lithium ion battery. The method is simple to operate, does not add additional processing steps, and has almost no effect on battery cost.

[0028] 3. The lithium battery prepared by the present invention can increase the battery storage life, reduce self-discharge, and achieve a balance between high specific energy, high power and long storage life. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of a cylindrical lithium battery;

[0030] Figure 2 The battery is charged to a negative state before the first voltage U1;

[0031] Figure 3 Charging the battery to a negative state between a first voltage U1 and a second voltage U2;

[0032] Figure 4 It is the dQ / dV~V curve;

[0033] Figure 5 It is a schematic diagram of a cylindrical battery cell;

[0034] In the figure, 100 is a battery shell, 110 is a battery cap, 120 is a battery shell bottom, 200 is an insulating medium, 300 is a battery cell, 310 is a positive electrode, 311 is a positive electrode tab, 320 is a negative electrode, 321 is a negative electrode tab, 322 is a negative electrode current collector copper foil, 323 is a negative electrode graphite active material, 324 is a porous conductive material, 325 is a lithium deposition layer, and 350 is a separator. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0036] The present invention provides a cylindrical lithium battery, which comprises a battery housing, a battery cap, a battery core, and an electrolyte. The battery core is composed of a positive electrode, a negative electrode, and a diaphragm, wherein:

[0037] The active material of the positive electrode is a coated high-nickel transition metal oxide material;

[0038] The coated high-nickel transition metal oxide material is lithium nickel cobalt chromate (NCC, Li 1+x Ni y Co z Cr 1-x-y-zO2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), lithium nickel cobalt manganese oxide (NCM, Li 1+x Ni y Co z Mn 1-x-y-z O2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), lithium nickel cobalt aluminum oxide (NCA, Li 1+x Ni y Co z Al 1-x-y-z O2, 0≤x≤0.3, 0.5≤y≤1, 0≤z≤0.3, x+y+z≤1), the thickness of the TiNb2O7 coating layer is 0.1-10nm;

[0039] The positive electrode contains at least one of lithium-rich nickel oxide (Li2NiO2), lithium-rich cobalt oxide (Li6CoO4), lithium ferrite (Li5FeO4), lithium squarate (Li2C4O4), and lithium oxalate (Li2C2O4), and the content thereof is 0 to 20 wt%.

[0040] The active material of the negative electrode is graphite, and the negative electrode is composed of a first coating and a second coating. When the battery is charged to between a first voltage U1 and a second voltage U2, a third coating, a metal lithium layer, is formed inside the second coating of the negative electrode and on the surface of the negative electrode;

[0041] The first coating is a graphite material with a D50 of 8 to 17 μm;

[0042] The surface of the first coating is covered with a second coating, the second coating is a porous conductive material with a porosity of 40% to 99%;

[0043] The porous conductive material includes but is not limited to activated carbon, carbon black, carbon fiber, carbon cloth, conductive polymer, metal porous material, metal organic framework;

[0044] The first voltage U1 is 3.85V to 4.00V, and the second voltage U2 is 4.1V to 4.3V;

[0045] The method for determining the first voltage U1 is as follows: the battery is charged to U2 at 0.1C after liquid injection, and the charging curve is plotted as dQ / dV to V. When the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85V to 4.00V, the voltage at this time is the first voltage U1;

[0046] The method for forming the third coating metal lithium layer inside the second coating layer in the negative electrode and on the surface of the negative electrode is as follows: during the charging formation process, lithium is electrochemically deposited on the surface of the negative electrode, and the thickness of the formed metal lithium layer is 1 to 5 μm;

[0047] The battery N / P ratio is 0.9 to 1.1;

[0048] The electrolyte contains fluorinated anhydride compounds, the addition amount of which is 0.1-5%;

[0049] The fluorinated anhydride compounds include but are not limited to fluorinated acetic anhydride, fluorinated succinic anhydride, fluorinated glutaric anhydride, fluorinated maleic anhydride, and fluorinated benzoic anhydride.

[0050] A method for preparing the above-mentioned lithium battery, the method comprising the following steps:

[0051] Step S1, mixing the positive electrode active material with the conductive agent and the adhesive evenly and coating the mixture on an aluminum foil, and rolling and cutting the mixture into a positive electrode;

[0052] Step S2, the negative electrode active material is mixed with the conductive agent and the adhesive and then coated on the copper foil, and then a porous conductive layer is coated on the surface after drying, and then the negative electrode is made by roller pressing and slitting, and the battery N / P ratio is 0.9-1.1. The battery is formed, and a lithium deposition layer is formed on the surface of the negative electrode in the range of 3.85-4.00V;

[0053] Step S3, winding the positive and negative electrodes and the separator into a cylindrical battery cell, and sequentially performing shelling, cap welding, liquid injection, sealing, and cleaning;

[0054] Step S4, take the battery after injection and charge it at 0.1C to U2, where U2 ranges from 4.1 to 4.3V, preferably 4.2V, plot the charging curve dQ / dV to V, and perform data processing to obtain a smooth curve, and observe the voltage at which the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85 to 4.00V, which is the first voltage U1;

[0055] Step S5, after the battery is filled with liquid, it is allowed to stand for 24 to 72 hours, then charged at a constant current of 0.05C for 1 hour, then charged at a constant current of 0.1C to a first voltage U1, allowed to stand for 10 to 30 minutes, discharged at a constant current of 0.1C to 2.75V, allowed to stand for 10 to 30 minutes, charged at a constant current of 0.2C to a first voltage U1, then charged at a constant current of nC to a second voltage U2, where nC is 0.3 to 2C, switched to constant voltage charging until the current is ≤0.02C, and ended.

[0056] In the above preparation method, the positive and negative electrodes are first prepared according to conventional processes, wherein the negative electrode is coated for the second time after the first coating is completed, the purpose is to cover a high-porosity conductive layer on the graphite surface, which can serve as the structural framework of the metal lithium layer. Through reasonable electrode design and N / P ratio, the distribution of active lithium in the positive and negative electrodes is regulated to achieve the appearance of a lithium deposition layer at the negative electrode in the range of 3.85V to 4.00V. According to conventional processes, winding into shells, cap welding, liquid injection, sealing, cleaning, etc. are carried out to form cylindrical batteries. Fluorinated anhydride compounds are specially added to the electrolyte, which can absorb trace moisture in the electrolyte and the battery core, and can also affect the electrode interface and the morphology of metal lithium during the formation process, so as to achieve a stable electrode interface, which is conducive to long-term storage life.

[0057] In the above preparation method, step S4 is to accurately obtain the first voltage U1 value of this batch. According to the battery design, the U1 value should be between 3.85V and 4.0V. The voltage at which the negative electrode is about to precipitate lithium can be determined by the dQ / dV~V curve. This voltage is the first voltage U1. That is to say, when the battery is charged to U1, no lithium precipitation occurs. After the voltage exceeds U1, lithium precipitation gradually begins and is deposited on the surface of the negative electrode. The precipitated metallic lithium has poor reversibility, and repeated charging and discharging will cause loss of active lithium. In the formation stage, the battery will undergo redox reactions on the positive and negative electrode surfaces to generate SEI films to protect the electrode interface. Therefore, the battery is discharged after the first charge to the first voltage U1 in order to form a perfect SEI film. The second charge is to fill the battery and obtain a smooth lithium metal deposition layer. In the first stage, the battery is charged to the first voltage U1 at 0.2C. This process can improve and repair the SEI film again. After reaching the first voltage U1, the battery continues to charge to deposit a metal lithium layer at the negative electrode. The state of lithium deposition can be controlled by controlling the charging rate. 1C charging is preferred. Since lithium deposition will react with the electrolyte, fast charging is beneficial to reduce the reaction rate, so that the formed lithium deposition layer is uniform and smooth. The interface is then passivated through battery aging, which greatly reduces the self-discharge rate of the battery.

[0058] In the above preparation method, the cylindrical lithium battery is a one-time reserve lithium battery with long-term high-charge storage, maintenance-free, no activation required, and immediate response. During the discharge process of the battery, the first deposited metal lithium layer loses electrons to form lithium ions, which enter the positive electrode through the electrolyte. The discharge process at this time is similar to that of a metal lithium battery, but because the copper foil, graphite layer, and second coating are current collectors at this time, the kinetics are better than that of a lithium metal battery. Subsequently, the lithium ions in the LiC6 inside the graphite negative electrode are released. The discharge process at this time is consistent with that of a lithium-ion battery, so the rate performance of the battery is significantly better than that of the original battery using a lithium metal negative electrode. In addition, the battery has the function of repeated charge and discharge in an emergency state, and can be used as a secondary battery, which has significant advantages over primary batteries.

[0059] Embodiment 1:

[0060] This embodiment provides a cylindrical lithium battery, which includes a battery housing 100, a battery cap 110, a battery cell 300 and an electrolyte. The battery cell 300 is composed of a positive electrode 310, a negative electrode 320 and a separator 350. The negative electrode contains a first coating and a second coating. When the battery is charged to a voltage between a first voltage U1 and a second voltage U2, a third coating, a metal lithium layer, is formed inside and on the surface of the second coating of the negative electrode, wherein:

[0061] (1) Positive electrode 310: Li-rich NCA (LiNb2O7) with a TiNb2O7 coating layer with an initial efficiency of 80% 1.1 Ni 0.8 Co 0.07 Al 0.03 O2) material is the positive electrode active material, the thickness of the TiNb2O7 coating layer on the material surface is 1nm, and it is mixed and stirred evenly with the binder PVDF and the conductive agent Super-P in NMP at a mass ratio of 95:2:3 to form a positive electrode slurry, and then coated on both sides of the aluminum foil, and after roller pressing and slitting, the positive electrode 310 is made.

[0062] (2) Negative electrode 320: Graphite is used as the negative electrode active material, and is mixed and stirred evenly with a binder PVDF in NMP at a mass ratio of 97:3 to form a negative electrode slurry, which is then coated on both sides of a copper foil with an N / P ratio of 1. After drying, an activated carbon layer is sprayed on the graphite surface, and the negative electrode 320 is formed after roller pressing and slitting.

[0063] (3) Separator 350: A polyolefin separator with a thickness of 16 μm was used.

[0064] (4) Production of the battery cell 300: The positive electrode 310, the separator 350 and the negative electrode 320 obtained above are welded to the positive electrode tab 311 and the negative electrode tab 321 by using a winding and welding integrated machine and then wound to obtain the battery cell 300;

[0065] (5) Place the battery cell 300 into a nickel-plated stainless steel battery case 100, weld the negative electrode tab 321 to the battery case bottom 120, place an insulating medium 200 on the top of the battery cell, and weld the positive electrode tab 311 to the battery cap 110;

[0066] (6) Inject 1.2 mol / L LiFP6-EC / DMC / EMC (volume ratio 1:1:1) + 2% VC + 2% PS + 0.5% TFSA electrolyte, and finally complete the battery sealing.

[0067] (7) After the injection, the battery is charged at 0.1C to a second voltage of 4.2V. The charging curve is plotted as dQ / dV-V, and the data is properly processed to obtain a smooth curve. It is observed that the voltage at which the dQ / dV value first drops below 2500mAh / V in the range of 3.85-4.00V is 3.9V, which is the first voltage U1.

[0068] (8) After the battery is filled and left to stand for 24 to 72 hours, it is first charged at a constant current of 0.05C for 1 hour, then charged at a constant current of 0.1C to a first voltage of 3.9V, left to stand for 10 to 30 minutes, discharged at a constant current of 0.1C to 2.75V, left to stand for 10 to 30 minutes, charged at a constant current of 0.2C to a first voltage of 3.9V, then charged at a constant current of 1C to a second voltage of 4.2V, switched to constant voltage charging until the current is ≤0.02C, and then ended.

[0069] Example 2

[0070] This embodiment provides a cylindrical lithium battery, which includes a battery housing 100, a battery cap 110, a battery cell 300 and an electrolyte. The battery cell 300 is composed of a positive electrode 310, a negative electrode 320 and a separator 350. The negative electrode contains a first coating and a second coating. When the battery is charged to a voltage between a first voltage U1 and a second voltage U2, a third coating, a metal lithium layer, is formed inside and on the surface of the second coating of the negative electrode. The specific preparation steps are as follows:

[0071] (1) Positive electrode 310: NCA (LiNi) with a TiNb2O7 coating layer 0.8 Co 0.15 Al 0.05 O2) is the positive electrode active material, the thickness of the TiNb2O7 coating layer is 3nm, the positive electrode active material and lithium quartz, binder PVDF and conductive agent Super-P are mixed and stirred evenly in NMP at a mass ratio of 90:5:2:3 to form a positive electrode slurry, and then coated on both sides of aluminum foil, and after roller pressing and slitting, the positive electrode 310 is made.

[0072] (2) Negative electrode 320: Graphite is used as the negative electrode active material, and is mixed and stirred evenly with a binder PVDF in NMP at a mass ratio of 97:3 to form a negative electrode slurry, which is then coated on both sides of a copper foil with an N / P ratio of 1. After drying, an activated carbon layer is sprayed on the graphite surface, and the negative electrode 320 is formed after roller pressing and slitting.

[0073] (3) Separator 350: A polyolefin separator with a thickness of 16 μm was used.

[0074] (4) Production of battery cell 300: The positive electrode 310, separator 350 and negative electrode 320 obtained above are welded to the positive electrode tab 311 and the negative electrode tab 321 by a winding and welding integrated machine and then wound to obtain a battery cell 300.

[0075] (5) Place the battery cell 300 into a nickel-plated stainless steel battery case 100 , weld the negative electrode tab 321 to the battery case bottom 120 , place an insulating medium 200 on the top of the battery cell, and weld the positive electrode tab 311 to the battery cap 110 .

[0076] (6) Inject 1.2 mol / L LiFP6-EC / DMC / EMC (volume ratio 1:1:1) + 2% VC + 2% PS + 0.5% TFSA (tetrafluorosuccinic anhydride) electrolyte, and finally complete the battery sealing.

[0077] (7) After the injection, the battery is charged at 0.1C to a second voltage of 4.2V. The charging curve is plotted as dQ / dV-V, and the data is properly processed to obtain a smooth curve. It is observed that the voltage at which the dQ / dV value first drops below 2500mAh / V in the range of 3.85-4.00V is 3.88V, which is the first voltage U1.

[0078] (8) After the battery is filled and left to stand for 24 to 72 hours, it is first charged at a constant current of 0.05C for 1 hour, then charged at a constant current of 0.1C to a first voltage of 3.88V, left to stand for 10 to 30 minutes, discharged at a constant current of 0.1C to 2.75V, left to stand for 10 to 30 minutes, charged at a constant current of 0.2C to a first voltage of 3.88V, then charged at a constant current of 1C to a second voltage of 4.2V, switched to constant voltage charging until the current is ≤0.02C, and then ended.

[0079] Comparative Example 1

[0080] (1) A cylindrical lithium battery was prepared according to the methods (1) to (6) in Example 1.

[0081] (2) After the battery is filled with liquid and left to stand for 24 to 72 hours, it is charged to 4.2V at a constant current of 0.1C, left to stand for 10 to 30 minutes, discharged to 2.75V at a constant current of 0.1C, left to stand for 10 to 30 minutes, and charged to 4.2V at a constant current of 0.2C.

[0082] Comparative Example 2

[0083] The battery was prepared and formed according to Comparative Example 1, except that the positive electrode 310 used NCA as the positive electrode active material, mixed and stirred evenly with the binder PVDF and the conductive agent Super-P in NMP at a mass ratio of 95:2:3 to form a positive electrode slurry, which was coated on both sides of the aluminum foil and rolled and cut to form the positive electrode 310. The N / P ratio was 1.1.

[0084] Comparative Example 3

[0085] The battery was prepared and formed according to Comparative Example 1, except that the negative electrode 320 was a metal lithium strip with a thickness of 50 μm.

[0086] The reserve lithium batteries with a rated capacity of 2.5Ah developed in the above Examples 1 to 2 and Comparative Examples 1 to 3 were tested for capacity and voltage respectively, and then stored at room temperature and at a high temperature of 55°C for 6 months. After storage, the open circuit voltage was measured first, and different batteries were taken for 0.2C capacity test and 5C rate discharge test. The test results are shown in Table 1.

[0087] Table 1

[0088]

[0089] As can be seen from Table 1, different cathode material formulations are used in Example 1 and Example 2, but the actual effects are similar. In Example 1, a coated lithium-rich NCA material is used, and the excess lithium can achieve negative electrode lithium replenishment during the first charging process. In Example 2, the same effect can be achieved by adding a lithium replenisher. The first voltage U1 is controlled between 3.85 and 4.00V, and through the optimized formation process, the first charge and discharge is carried out between 2.75 and 3.9V, there is no problem of lithium deposition, and a good SEI film can be formed to protect the electrode. In the second charging process, a small current charge can be performed first to further repair the SEI. After 3.9V, by increasing the charging current, not only can the morphology and structure of lithium deposition be controlled, but also the occurrence of lithium surface side reactions can be inhibited, and the activity loss of metal lithium can be reduced. After the formation is completed, the deposited metal lithium with a smooth surface reacts with the electrolyte to achieve surface passivation, thereby protecting the metal lithium layer, so that the battery has the best discharge capacity and rate performance regardless of whether it is stored at room temperature or at high temperature. The capacity retention rate of storage at room temperature for 6 months can reach more than 99%, and the capacity retention rate of storage at high temperature of 55℃ also reaches 92%. The battery shows good rate performance. After storage at room temperature, the 5C discharge capacity reaches 2.5Ah, and after storage at high temperature of 55℃, the 5C discharge capacity still reaches 2.3Ah.

[0090] The preparation method of the cylindrical lithium battery in Comparative Example 1 is the same, but the formation process is different, which is mainly used to compare the impact of the formation process. The conventional formation process used has the lowest capacity of the battery because a large amount of lithium deposition occurs at the negative electrode during the first charging process during the formation process, and a part of the lithium undergoes a passivation reaction and loses activity after discharge and recharging, resulting in the loss of active lithium. At the same time, due to the use of a small current of 0.2C in the second charging stage, the side reaction products of the deposited lithium metal layer are relatively large, and the specific surface area is large, which is not conducive to long-term storage. Therefore, its room temperature storage capacity, high temperature storage capacity and 5C discharge capacity are all inferior to those of Example 1 and Example 2.

[0091] Comparative Example 2 is a conventional lithium-ion battery design and formation process, which is mainly used to compare the effects of lithium deposition layer on self-discharge and rate performance. There is no metal lithium protection layer on the negative electrode surface, and the large surface area of ​​graphite is fully exposed, and the reaction activity with the electrolyte is large. There is a large self-discharge during storage at room temperature and high temperature. The remaining capacity after 6 months of storage at room temperature is only 2.493Ah, with a retention rate of 94%, while the remaining capacity after 6 months of storage at high temperature of 55°C is only 2.174Ah, with a retention rate of only 82%. Obviously, it does not have long-term storage characteristics.

[0092] Comparative Example 3 is a lithium primary battery design, mainly used to compare storage performance and rate performance. It can be seen that metal lithium is the negative electrode battery. Due to the excessive state of negative electrode lithium, the battery capacity is determined by the positive electrode, and the metal lithium also reaches a relatively stable state after passivation. The self-discharge rate is close to that of Example 1 and Example 2, but its rate performance is poor. Since metal lithium acts as both a current collector and an active material, the discharge polarization is large, and the 5C discharge capacity retention rate is only about 50%. After high-temperature storage, due to the influence of the lithium passivation film, the rate performance is further reduced.

Claims

1. A cylindrical lithium battery, comprising a battery housing, a battery cap, a battery core, and an electrolyte, wherein the battery core is composed of a positive electrode, a negative electrode, and a diaphragm, characterized in that The active material of the positive electrode is a coated high-nickel transition metal oxide material; the active material of the negative electrode is graphite, and the negative electrode contains a first coating and a second coating. When the battery is charged to between a first voltage U1 and a second voltage U2, a third coating - a metallic lithium layer is formed inside and on the surface of the second coating of the negative electrode; the first coating is a graphite material, and the second coating is a porous conductive material; the first voltage U1 is 3.85V~4.00V, and the second voltage U2 is 4.1V~4.3V.

2. The cylindrical lithium battery according to claim 1, characterized in that The coated high-nickel transition metal oxide material is one or more of lithium nickel cobalt chromate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminum oxide having a TiNb2O7 coating layer, and the thickness of the TiNb2O7 coating layer is 0.1 to 10 nm.

3. The cylindrical lithium battery according to claim 1, characterized in that The positive electrode contains at least one of lithium-rich nickel oxide, lithium-rich cobalt oxide, pentalithium ferrite, lithium squarate and lithium oxalate, and the content thereof is 0-20wt%.

4. The cylindrical lithium battery according to claim 1, characterized in that The battery N / P ratio is 0.9 to 1.

1.

5. The cylindrical lithium battery according to claim 1, characterized in that The porosity of the porous conductive material is 40-99%, and the D50 of the graphite material is 8-17 μm.

6. The cylindrical lithium battery according to claim 4, characterized in that The porous conductive material is one of activated carbon, carbon black, carbon fiber, carbon cloth, conductive polymer, metal porous material and metal organic framework.

7. The cylindrical lithium battery according to claim 1, characterized in that The method for determining the first voltage U1 is: take the battery after injection and charge it at 0.1C to U2, plot the charging curve dQ / dV~V, and when the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85V~4.00V, the voltage at this time is the first voltage U1.

8. The cylindrical lithium battery according to claim 1, characterized in that The method for forming the third coating metal lithium layer inside and on the surface of the negative electrode second coating is that lithium is electrochemically deposited on the negative electrode surface during the charging formation process, and the formed metal lithium layer has a deposition thickness of 1 to 5 μm.

9. The cylindrical lithium battery according to claim 1, characterized in that The electrolyte contains a fluorinated acid anhydride compound, which is one of fluorinated acetic anhydride, fluorinated succinic anhydride, fluorinated glutaric anhydride, fluorinated maleic anhydride and fluorinated benzoic anhydride, and the added amount is 0.1-5%.

10. A method for preparing the cylindrical lithium battery according to any one of claims 1 to 9, the method comprising the following steps: Step S1, mixing the positive electrode active material with the conductive agent and the adhesive evenly and coating the mixture on an aluminum foil, and rolling and cutting the mixture into a positive electrode; Step S2, the negative electrode active material is mixed with the conductive agent and the adhesive and then coated on the copper foil, and then a porous conductive layer is coated on the surface after drying, and then the negative electrode is made by roller pressing and slitting, and the N / P ratio of the battery is 0.9-1.

1. The battery is formed, and a lithium deposition layer is formed on the surface of the negative electrode in the range of 3.85-4.00V; Step S3, winding the positive and negative electrodes and the separator into a cylindrical battery cell, and sequentially performing shelling, cap welding, liquid injection, sealing, and cleaning; Step S4, take the battery after injection and charge it at 0.1C to U2, where U2 ranges from 4.1 to 4.3V, preferably 4.2V, plot the charging curve dQ / dV to V, and perform data processing to obtain a smooth curve, and observe the voltage at which the dQ / dV value drops below 2500mAh / V for the first time in the range of 3.85 to 4.00V, which is the first voltage U1; Step S5, after the battery is filled with liquid, it is allowed to stand for 24 to 72 hours, then charged at a constant current of 0.05C for 1 hour, then charged at a constant current of 0.1C to a first voltage U1, allowed to stand for 10 to 30 minutes, discharged at a constant current of 0.1C to 2.75V, allowed to stand for 10 to 30 minutes, charged at a constant current of 0.2C to a first voltage U1, then charged at a constant current of nC to a second voltage U2, where nC is 0.3 to 2C, switched to constant voltage charging until the current is ≤0.02C, and ended.